Aviation, Carbon, and the Clean Air Act - Richardson, Nathan (Columbia Journal of Environmental Law, 2019)
Can CAA regulation achieve aviation emissions regulations significant enough to establish equivalency with E.U. policy while remaining cost-effective and politically acceptable? Fully answering this question requires judgments about the range of options realistically available to the EPA in the current U.S. political environment and about the range of policies the E.U. would consider “equivalent”—judgments that would be, at best, informed guesses. But the core part of the question is legal. Specifically, what tools are available to the Agency under the CAA to regulate aviation emissions, and how might they be used for GHGs? This Article is an attempt to answer that core legal question. The Agency’s powers to address aviation GHGs under the Act have not been thoroughly studied. A few court decisions, EPA documents, and petitions to the Agency have looked at the issue or aspects of it, but none is a comprehensive assessment. One relatively brief scholarly treatment exists, and although it is a useful introduction to many of the relevant issues, much has changed since it was published in 2009. This Article also reaches different conclusions on several points, as noted below. EPA regulation of aviation GHG emissions under the CAA was the subject of recent litigation. However, that litigation concerned whether the Agency must regulate such emissions. This threshold issue is relevant, but both parties to the litigation agree that the EPA has authority to regulate aviation emissions. Moreover, the suit did nothing to clarify how the Agency could regulate, whether it chooses to do so or is compelled. It is this latter question that this Article seeks to answer. In short, the CAA does provide the EPA with substantial authority and flexibility to regulate aviation GHG emissions. Doing so will require the Agency to depart from its traditional use of this authority, but neither the statute nor international law appears to stand in the way. The Act further appears to give the Agency authority to implement smart regulation in the form of performance standards that give compliance flexibility to industry and perhaps allow limited use of market-based mechanisms. Political and administrative challenges remain for the EPA, however.